Pengaruh Aktivitas Pemasaran Media Sosial Terhadap Ekuitas Merek dan Loyalitas Merek Pada Konsumen Muslim Marketplace Lazada - Nailufar, Wilda; Yoestini, Yoestini (Jurnal Ilmiah Ekonomi Islam, 2023)
This research aims to determine the influence of Social Media Marketing Activities on Brand Equity and Brand Loyalty among Lazada Marketplace ConsumersTo gain a more comprehensive understanding of social media marketing from brands, it is important to examine the influence of social media marketing activities on brand building in various product and service contexts.The results of the analysis show that social media marketing activities have a significant effect on brand awareness, brand image and brand loyalty. These results are in accordance with the results of research conducted by Ismail, (2017), Seo&Park (2018), Bilgin (2018), and Malarvizhi, et al. (2022). The SOR theory underlies this research where every process of social media's effects on individuals begins with attention to several media messages. This shows that the public receives a stimulus, namely consumer exposure to a brand's social media which then has an influence on the public and produces a response including trust, purchase commitment and loyalty to a brand.